Characterization of a novel snake venom component: Kazal-type inhibitor-like protein from the arboreal pitviper Bothriechis schlegelii - Fernández Ulate, Julián (2016)
Snake venoms are composed mainly of a mixture of proteins and peptides. Notably, all snake venom toxins have been assigned to a small number of protein families. Proteomic studies on snake venoms have recently identified the presence of Kazal-type inhibitor-like proteins in the neotropical arboreal snakes Bothriechis schlegelii and Bothriechis supraciliaris. In the present study, a Kazal-type component from B. schlegelii, named Kazal-type inhibitor-like protein (KTIL), has been completely sequenced and characterized for the first time. This protein, which contains 54 amino acid residues, shows sequence similarity to the third domain of the ovomucoid from avian species, which is a Kazal-like domain. KTIL did not inhibit the enzymatic activity of various serine proteinases at pH = 7.2 or pH = 8.0, but partially inhibited the activity of trypsin at pH = 5.4, and the only toxic effect in mice observed after different in vivo tests was the induction of footpad edema. KTIL was not lethal when injected in mice or chickens. The presence of Kazal-type proteins and mRNA only in species of the genus Bothriechis suggests a genus recruitment event in the early-Middle Miocene, the estimated time of emergence of this clade.